Activation of peroxymonosulfate into amoxicillin degradation using cobalt ferrite nanoparticles anchored on graphene (CoFe2O4@Gr). (3rd April 2021) - Lashkaryani, Elham Babaei; Kakavandi, Babak; Kalantary, Roshanak Rezaei; Jafari, Ahmad Jonidi; Gholami, Mitra
Abstract: The study focused on the catalytic activation of peroxymonosulfate (PMS) using cobalt ferrite nanoparticles decorated on graphene (CoFe2 O4 @Gr) into amoxicillin (AMX) degradation-based on sulfate radicals. Oxidation experiments were performed at different experimental variables such as PMS dosages, pH, reaction time and various concentrations of catalyst and AMX. CoFe2 O4 @Gr has a good magnetic response and rapidly separated from aquatic media. It also showed a significant catalytic activity in decomposition of PMS molecules. At optimum conditions, 99.27, 83.1 and 61.11% of AMX, chemical oxygen demand and total organic carbon were removed during 60 min reaction, respectively.